Archetypes of traditional archery in Khakasya (Sayano-Altai) Tashtyky Culture - Türkmen, Mehmet; Ziyagil, Mehmet Akif (Nova Science Publishers, Inc., 2024)
In this research, it will be tried to convey information about the archeological findings and petroglyph images (pictures on rocks) about the types of bow and arrowheads in the petroglyphs of the Tashtyk ('Taştik') culture, which occurred between the 3rd and 5th centuries BC in Southern Siberia. While carrying out the three projects written in the footnote about traditional sports and games, our field studies in South Siberia, which is affiliated to the Russian Federation, constitute the materials of the research. During this fieldwork, rock paintings, kurgan finds from the Tashtyk (ancient Kyrgyz) period, which are not related to traditional sports games but related to arrow sports, bow and arrow types exhibited in museums of that period, and especially arrowheads, will be modestly presented with this research. The archaic images of archery, considered the prototype of archery, and archery in Tashtyk petroglyphs, have been instrumental in the nourishment, shelter, transportation and protection of the peoples where they existed throughout history, the culture that they built, their existence in the culture they built, and the change and transformation of the culture. In this research, archery as a social phenomenon; it is aimed to explain the subject in the direction of tracing the daily life evolving from the sacred to the secular. In the study, the terminology of Tashtyk culture; studies on the subject and its pioneers; to which clan or peoples the Tashtyk culture belongs; Rock paintings in the Republic of Khakassia and the connection of bow and arrowheads exhibited in museums with the archetype of today's traditional archery will be examined. The findings obtained in the research will be summarized in the conclusion part. © 2024 Nova Science Publishers, Inc. All rights reserved.
Keywords: Ancient bow and arrowheads; Indigenous peoples; Iron age; Petroglyphs; Southern Siberia; Tashtyk culture